Analysis of Performance Measurement using Performance Prism Method (Case Study in PT. Inti Luhur Fuja Abadi, Pasuruan) - Dania, Wike Agustin Prima; Santoso, imam; Sari, Rheysa Permata (Jurnal Teknologi Pertanian, 2012)
Performance prism method is used to improve performance measurement method in PT Inti Luhur Fuja Abadi Pasuruan. The design and performance measurement methods used for Performance Prism can reflect the needs and desires of each stakeholder identified in the form of goals (objectives). Performance measurement is an integrated measurement, covering all aspects of the company (stakeholders) involving stakeholder satisfaction and stakeholder contribution to the company. Performance measurement in this study is also supported by several methods such as weighting by Hierarchy Analytic Process (AHP) to determine the scale of priority value of each Key performance Indicator (KPI), Scoring System Objectives Matrix method (OMAX) to determine performance indicator, and Traffic Light System to determine which KPI that need improvement based on color. From this result, it can be seen that there are four KPIs that need improvement, which are, customer suggestion (C-4), core competition application (E-6), payment time (S-1), bargaining processing (S-2). Overall, the company’s performance in cooperate stage is good with the value is 9.46326. Keywords: key performance indicator, analytic hierarchy process (AHP), objectives matrix (OMAX), traffic light system